Space Charge Field Generation and Thermal Effect in a Dye-Doped Twisted Nematic Liquid Crystal Cell - Amor, R.; Palima, D.; Daza, M.; Domingo, Z. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
Excerpt Nematic liquid crystals exhibit long-range orientational order of the axes of the molecules, the average direction being described by the nematic director n. These materials are known for their large nonlinear optical properties (Tabiryan et al., 1986; Palffy-Muhoray, 1990; Khoo, 1994), possess very broadband (0.4 mm-12 mm) birefringence and transparency, and have a large susceptibility to ac, dc and optical fields. These properties combine to make nematic liquid crystals ideal materials for image sensing, display and processing devices (Khoo & Wu, 1993; Khoo, 1994).